2021
DOI: 10.1101/2021.06.25.449885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prophages in the infant gut are largely induced, and may be functionally relevant to their hosts

Abstract: Background: Bacteriophages are the most abundant biological entity on the planet, and are key components of any ecosystem they are present in. The gut virome is increasingly being implicated in disease states although these studies largely focus on lytic phages in adults. Here we identify prophages from a large infant cohort and investigate their potential functions. Results: We identified 10645 vOTUs from 662 metagenomes. No core virome was found: the most prevalent vOTU was identified in 70% of the samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…In support of the long-term memory role of distal CRISPR spacers, we found that the fraction of spacers targeting lysogenic phages systematically increases from the leading to the trailing end of the array (Figure 3d). Considering the high rates of lytic activity and CRISPR spacer turnover that characterize the infant gut, and the possible contribution of early phagebacteria interactions to shaping the adult gut microbiome (13,(89)(90)(91), an intriguing possibility might be that long-term memory spacers were selected during the consolidation of a coexisting community of MGE and bacteria in the first years of age.…”
Section: Selection Promotes Long-term Immunity Against Endemic Mgementioning
confidence: 99%
“…In support of the long-term memory role of distal CRISPR spacers, we found that the fraction of spacers targeting lysogenic phages systematically increases from the leading to the trailing end of the array (Figure 3d). Considering the high rates of lytic activity and CRISPR spacer turnover that characterize the infant gut, and the possible contribution of early phagebacteria interactions to shaping the adult gut microbiome (13,(89)(90)(91), an intriguing possibility might be that long-term memory spacers were selected during the consolidation of a coexisting community of MGE and bacteria in the first years of age.…”
Section: Selection Promotes Long-term Immunity Against Endemic Mgementioning
confidence: 99%
“…) 49 known for its diversity-generating retroelements, and it has been extensively described in a parallel provirome study performed on the same samples 50 .…”
Section: Undescribed Viral Families Dominate the Infant Gut Viromementioning
confidence: 99%
“…The Copenhagen Prospective Studies on Asthma in Childhood 2010 (COPSAC) dataset consisted of 662 paired samples (refs. 33,34 ) and the Diabimmune dataset contained 112 paired samples 35 . Each of the two datasets included a list of curated viral species, 10,021 and 328 respectively, that we used here as our gold standard for training and testing our tool.…”
Section: Resultsmentioning
confidence: 99%
“…The Copenhagen Prospective Studies on Asthma in Childhood 2010 (COPSAC) dataset consisted of 662 paired samples obtained at age 1 year from an unselected childhood cohort (refs. 33,34 ). The COPSAC study was conducted in accordance with the guiding principles of the Declaration of Helsinki and was approved by the Capital Region of Denmark Local Ethics Committee (H-B-2008-093), and the Danish Data Protection Agency (2015-41-3696).…”
Section: Methodsmentioning
confidence: 99%